RFI Mitigation with BETA - Bannister, K.; Hellbourg, Gregory; Hotan, A. (2016)
The Boolardy Engineering Test Array (BETA) is a 6 antenna interferometer, with each antenna having a 188-element phased array feed at the prime focus. Here we attempt to mitigate the affect of radio frequency interference (RFI) by updating the beam weights using a projection algorithm applied to the measured single-dish array covariance matrix. We observe an astronomical source at 1225 MHz, which contains substantial interference from the GPS L2 band, and compare a number of different projection algorithms by looking at the affect on correlated visibilities, and on the resulting images. The RFI projection algorithms perform remarkably well, yielding a promising future for this technique.